2018
DOI: 10.1186/s13065-018-0476-4
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, antioxidant activity and antibacterial mechanism of action from Marsilea minuta leaf hexane: methanol extract

Abstract: BackgroundIn the present study, hexane: methanol (50:50) leaf extract of Marisela minuta has been evaluated for its chemical composition, antioxidant effect and the antimicrobial mechanism of action against food borne pathogenic bacteria.ResultsThe phytochemical evaluation of extract by GC/MS revealed the major abundance of benzoic acid-4-ethoxyethyl ester (43.39%) and farnesol acetate (18.42%). The extract exhibited potential antioxidant and free radical scavenging properties with promising antibacterial acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…In this study, the SEM, relative electric conductivity, membrane potential assays indicated that the permeability of bacteria membrane would be increased, and then the contents such as nucleic acids, proteins and other substances within the cell leaked out. As biocatalysts, enzymes were necessary to biological metabolisms and affected by various of factors, and the activity of endoenzyme as one of the main factors can cause the death of bacterial cell [39][40][41] . Some studies indicated that ROS attack the unsaturated fatty acids in the cell membrane, and cause lipid peroxidation, eventually leading to the destruction of the cell membrane, which can induce the apoptosis of cells [42][43][44] .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the SEM, relative electric conductivity, membrane potential assays indicated that the permeability of bacteria membrane would be increased, and then the contents such as nucleic acids, proteins and other substances within the cell leaked out. As biocatalysts, enzymes were necessary to biological metabolisms and affected by various of factors, and the activity of endoenzyme as one of the main factors can cause the death of bacterial cell [39][40][41] . Some studies indicated that ROS attack the unsaturated fatty acids in the cell membrane, and cause lipid peroxidation, eventually leading to the destruction of the cell membrane, which can induce the apoptosis of cells [42][43][44] .…”
Section: Discussionmentioning
confidence: 99%
“…S. aureus infections cause various inflammatory reactions, and the widespread use of antibiotics in treatment has made aureus resistant to drugs [ 38 ]. Currently, some natural extracts have been found to inhibit the growth of S. aureus [ 39 , 40 ]. Natural polysaccharides have a weak ability to inhibit the growth of S. aureus , though their ability can be improved after chemical modifications [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to these observations, strong antifungal activity could be attributed to phenolic compounds ( Table 1). Possible modes of action of phenolic compounds have been reported in different reviews [51][52][53][54], however the mechanisms have not been completely elucidated. López-Malo et al in 2005 mentioned that the effect of phenolic compounds is concentration-dependent [51].…”
Section: Mic and Mfc Determinationmentioning
confidence: 99%
“…They could also interact with membrane proteins, causing a deformation in their structure and functionality [51]. Once the phenolic compound crossed the cellular membrane, interactions with membrane enzymes and proteins would cause an opposite flow of protons, affecting cellular activity [51][52][53][54].…”
Section: Mic and Mfc Determinationmentioning
confidence: 99%